Bibliometric Analysis of MSME Financing - Loso Judijanto (Westscience Press, 2026)
This study aims to map the intellectual structure and research trends in MSME financing through a bibliometric analysis of scientific publications indexed in the Scopus database. Using VOSviewer as the primary analytical tool, this research examines keyword co-occurrence, overlay visualization, density mapping, co-authorship networks, institutional collaboration, and country collaboration patterns to identify dominant themes and emerging research directions. The findings indicate that MSMEs remain the central focus within the financing literature, closely associated with financial inclusion, financial literacy, digital transformation, and entrepreneurial finance. The evolution of research shows a transition from traditional microfinance and banking perspectives toward digitally enabled and innovation-driven financing ecosystems. Density analysis highlights financial inclusion as a highly concentrated research area, while themes such as decentralized finance and risk management appear as emerging opportunities for future studies. Collaboration patterns reveal strong interconnectedness among authors and institutions, with significant contributions from Asian countries, particularly India, China, and the Philippines, reflecting the importance of MSMEs in developing economies. This study provides a comprehensive overview of the development, structure, and future research agenda of MSME financing literature, offering valuable insights for scholars, policymakers, and practitioners seeking to strengthen inclusive and sustainable financial systems for MSMEs.